From resolutions to action: how parliamentary diplomacy shapes EU foreign policy towards Taiwan - Reinhard Biedermann (Political Research Exchange)
This paper examines the increasing role of European parliamentary diplomacy (PD) in shaping EU foreign policy towards Taiwan amidst rising geopolitical tensions and recent corruption scandals. It analyses how PD, through mechanisms such as cross-loading, promotes the Europeanisation of EU foreign policy and member states’ positions regarding Taiwan. The study employs Claudio M. Radaelli’s Europeanisation framework to illustrate how PD contributes to constructing, diffusing, and institutionalizing formal and informal EU practices. Cross-loading is crucial for facilitating exchanges between EU and national parliamentary actors, thus enhancing the diffusion of policy ideas and coordination among like-minded member states. The analysis reveals that while Europeanisation primarily functions through horizontal mechanisms like cross-loading, PD bolsters the EU’s normative influence in foreign affairs, increasing visibility and fostering stronger bilateral ties, particularly with Taiwan. The study evaluates the impacts of PD on EU-Taiwan relations, demonstrating its role in promoting the Europeanisation of EU foreign policy and aligning member states’ foreign agendas. The paper concludes that despite recent challenges, parliamentary friendship groups and cross-loading are essential for advancing the EU’s foreign policy objectives and enhancing its external influence, especially with democratic partners like Taiwan.